2009
DOI: 10.1007/s00424-009-0681-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulatory aspects of the extracellular Ca2+-sensing receptor, CaR

Abstract: The capacity to sense and adapt to changes in environmental cues is of paramount importance for every living organism. From yeast to man, cells must be able to match cellular activities to growth environment and nutrient availability. Key to this process is the development of membrane-bound systems that can detect modifications in the extracellular environment and to translate these into biological responses. Evidence gathered over the last 15 years has demonstrated that many of these cell surface "sensors" be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 145 publications
(172 reference statements)
1
25
0
Order By: Relevance
“…Recent reports clearly point to a role for the CaSR as a regulator of early development and as a guardian of the homeostatic balance between proliferation and differentiation in adults [19,68,70,71,73,75,89,92]. The identification of CaSR mutations that cause FHH and hypocalcemia [93][94][95][96][97][98], and the recent discoveries implicating the dysregulation of CaSR signaling in many other diseases [99,[113][114][115][119][120][121][122][123][124], position the CaSR as a broad therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports clearly point to a role for the CaSR as a regulator of early development and as a guardian of the homeostatic balance between proliferation and differentiation in adults [19,68,70,71,73,75,89,92]. The identification of CaSR mutations that cause FHH and hypocalcemia [93][94][95][96][97][98], and the recent discoveries implicating the dysregulation of CaSR signaling in many other diseases [99,[113][114][115][119][120][121][122][123][124], position the CaSR as a broad therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The CaSR is highly expressed in the developing fetus, with the highest expression levels found in the central and peripheral nervous system, heart, lung and cartilage [68]. The developing fetus is hypercalcemic compared with the adult, with significantly higher levels of extracellular calcium found in cord blood as compared with maternal blood [69].…”
Section: Fetal Developmentmentioning
confidence: 99%
“…The metastasis of breast cancer cells to bone result in osteolysis and lead to the release of large quantities of Ca 2+ into the bone microenvironment (45,46). This Ca o 2+ can be a primary signaling molecule and act through the CaR that directly regulates multiple signaling pathways involved in breast cancer cell growth, proliferation, differentiation, apoptosis and migration (58,59), and through the Ca 2+ channels which elevate intracellular Ca 2+ (Ca i 2+ ) levels to modulate Ca 2+ -dependent proteins (60).…”
Section: + -Sensing Receptor and Breast Cancermentioning
confidence: 99%
“…The CaSR belongs to group C of the G-protein-coupled receptor superfamily (GPCRs) and has been demonstrated to be sensitive to a variety of metabolic signals including di-and trivalent cations (Ca 2+ , Mg 2+ , metals belonging to the lanthanides series such as La 3+ , etc. ), pH, ionic strength, aromatic amino acids (L-Phe, LTrp) and polyamines such as spermine (for reviews, see Chang and Shoback, 2004;Riccardi et al, 2009;Riccardi and Kemp, 2012). Genetic studies in humans have shown that the best documented role of the CaSR is in systemic homeostasis of extracellular free ionized Ca 2+ concentration [Ca 2+ ] o through the regulation of parathyroid hormone secretion by the parathyroid glands (Brown and MacLeod, 2001;Conigrave et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies in humans have shown that the best documented role of the CaSR is in systemic homeostasis of extracellular free ionized Ca 2+ concentration [Ca 2+ ] o through the regulation of parathyroid hormone secretion by the parathyroid glands (Brown and MacLeod, 2001;Conigrave et al, 2000). However, expression of the CaSR has been reported in many other specialized cells and tissues that are not primarily involved in [Ca 2+ ] o homeostasis, such as in the brain, skin and lungs, suggesting that the receptor might be involved in cellular functions other than divalent cation homeostasis (Hebert et al, 2004;Riccardi et al, 2009;Yano et al, 2004). The CaSR has been reported to be expressed in cells of the diffuse neuroendocrine system, such as endocrine pancreatic cells (Gray et al, 2006), intestinal cholecystokinin secreting cells (Wang et al, 2011), and in a subset of innervated sensory epithelial cells in taste buds (San Gabriel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%